Factors associated with hypertension among adults in Nepal as per the Joint National Committee 7 and 2017 American College of Cardiology/American Heart Association hypertension guidelines: A cross-sectional analysis of the demographic and health survey 2016 - Gupta, Rajat Das; Bin Zaman, Sojib; Wagle, Kusum; Crispen, Reese; Hashan, Mohammad Rashidul; Al Kibria, Gulam Muhammed (BMJ Journals, 2022)
This article was published in The BMJ Open [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2019-030206 The Journal's website is at: https://bmjopen.bmj.com/content/9/8/e030206